Tyranny of Corporate Dominance Exemplified by Food Supply in Modern-Day Britain - Hallsworth , Alan; Wong , Alfred (Journal of Law and Governance, 2015)
Food supply incorporates both production and distribution. During the past few decades, large corporations have steadily gained control over food supply. This increased dominance is a result of, among other things, the continuation of neoliberal free-market government policies. Because of the legal mandate of modern corporations, the psychopathic pursuit of profit for their shareholders is a natural undertaking. In particular, four multiples now control a significant segment of the grocery market in Britain. Because of such pervasive presence, the major multiples are shaping the preference and choices of the grocery buying public. Such corporate dominance is a form of tyranny whenever it limits the free will and choices of the population at large. Despite periodic vocal public indignation and outcries against such “abuses”, many middle income citizens continue to drive cars to large supermarkets to do virtually all their grocery shopping conveniently under “one roof”. The scope of action available to the public to redress this imbalance is greatly circumscribed.